Childhood sexual abuse: a longitudinal study of disclosures and denials - Hartman, Dana T. (Child maltreatment, 2023)
In legal cases regarding child sexual abuse (CSA), children have various options, such as to disclose or deny maltreatment. When interviewed in adulthood, their accounts may be consistent with their childhood responses. Alternatively, denial in childhood could be followed in adulthood by disclosure ("deferred disclosure"), confirming previous suspicions. Or the adults could possibly recant. We conducted a longitudinal study of CSA disclosures and denials (N = 99; Time 1 [T1], 3- to 16-year-olds). T1 CSA disclosures and denials at a forensic unit were compared to the individuals’ responses 20 years later (Time 2 [T2]. 22- to 37-years-old). We found that consistent disclosure was associated with being older at T1 and female. Deferred disclosure was significantly associated with greater T2 trauma-related symptoms. Corroboration and higher CSA severity predicted T2 recantation. Consistent denial was related to less severe CSA. Our findings add to knowledge about CSA disclosures, which affect legal pathways available to child victims.